Iran And Yemen; Study the Reflection of The Islamic Revolution of Iran On Yemen And Its Results (Journal of Advanced Research in Social Sciences, 2020)
The Islamic Revolution of Iran took place in 1789. Undoubtedly, this revolution had repercussions on its peripheral and semi-peripheral countries, and one of the semi-peripheral countries of Iran that were affected by the revolution was Yemen. Yemen changed with the beginning of the Arab Spring and protest movements were formed in it, the content of which was very close to the foundations of the Islamic Revolution of Iran. These protests led to the revolution and eventually to the victory of the Houthi movement in Yemen and the Ansar Allah movement. But what are the consequences of this event in Yemen in Yemen and the Islamic Republic of Iran? The purpose of this study is to check the results of the export of the Iranian revolution in Yemen. The research findings show that the Islamic Revolution of Iran was exported to Yemen and a very close relationship was established between Yemen and the Islamic Republic. The Yemeni revolution has had very positive results for the regime of the Islamic Republic of Iran, like the addition of Yemen to the axis of resistance, resistance to Saudi Islam, etc., but to the results that happened to Yemen itself, we can become independent. Yemen touched on freedom of action in deciding and choosing its destiny. Yemen is embroiled in a bloody war that is still going on, and the living and economic situation of the people in Yemen is worse than before. The method of the present study is qualitative and based on the analytical description.